2021
DOI: 10.48550/arxiv.2111.04657
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution efficiency and structure of complex networks

Abstract: Flow networks efficiently transport nutrients and other solutes in many physical systems, such as plant and animal vasculature. In the case of the animal circulatory system, an adequate oxygen and nutrient supply is not guaranteed everywhere: as nutrients travel through the microcirculation and get absorbed, they become less available at the venous side of the vascular network. Ensuring that the nutrient distribution is homogeneous provides a fitness advantage, as all tissue gets enough supply to survive while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This approach is simple and powerful, allowing for easy assessment of flow and pressure distribution within the system [4]. It also facilitates the study of network properties, such as robustness, hierarchy, and phenomena like network remodeling and tuning [5][6][7][8][9][10][11]. However, experiments have shown that natural flow networks can contain intrinsically nonlinear elements that do not conform to Ohm's law.…”
mentioning
confidence: 99%
“…This approach is simple and powerful, allowing for easy assessment of flow and pressure distribution within the system [4]. It also facilitates the study of network properties, such as robustness, hierarchy, and phenomena like network remodeling and tuning [5][6][7][8][9][10][11]. However, experiments have shown that natural flow networks can contain intrinsically nonlinear elements that do not conform to Ohm's law.…”
mentioning
confidence: 99%